Sistem Pengambilan Keputusan Untuk Mengetahui Kualitas Ginseng Jawa (Talinum Paniculatum Gaertn) Dan Ginseng Korea (Panax Ginseng) Sebagai Bahan Obat Herbal Dengan Menggunakan Metode AHP (Studi Kasus : “Sari Akar Ginseng” Banyuwangi) - Abdul Aziz (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Som Java (Talinum Paniculatum Gaertn) known as Java ginseng (Talinum Paniculatum Gaertn) is a medicinal plant species are often used as a raw material for medicine. Benefitscontained in som Java (Talinum Paniculatum Gaertn) is similar to Korean ginseng (PanaxGinseng) because of its chemical components are not much different. Korean ginseng(Panax Ginseng) ginseng including the most famous in society because of its high quality.But many people today who do not know the result of consuming one dose and dosingappropriate, so many consumers ginseng poisoned even death. Of this problem we need amodel that is able to classify and determine the content and criteria for Java that can beconsumed ginseng as a medicinal herb. Medel decision system using AHP (AnaliticalHierarchy Process) method was able to classify and determine the extent and content ofginseng Java (Talinum Paniculatum Gaertn) that can be used as a medicinal herb. Results obtained using the AHP (Analitical Hierarchy Process) method that Koreanginseng (Panax Ginseng) quality is still better than the Javanese ginseng  (TalinumPaniculatum Gaertn), Korean ginseng (Panax Ginseng) gained weight (0.67) and ginsengJava  (Talinum Paniculatum Gaertn) (0.28). but with the SAW method results korean ginseng(Panax Ginseng) weight (2.08) and ginseng Java  (Talinum Paniculatum Gaertn) (1.95)using the method of weighting the results of SAW (Simple Additive Weighting) overapproaching the facts, but using AHP (Analitical Hierarchy Process) method is moredetailed and clear.